Prolegomenon to the ontology of neoclassical philosophy - KRASNOV, A.S.; VOLCHKOVA, O.O. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The situation into which modern philosophy falls today is fundamentally different. Conceptual changes and shifts in modern philosophical science concern not only the revision of the reality but also the explanation of new categories and principles. This paper aims to reveal the main content, reflective models and the potential of neoclassical philosophy in the context of the formation of a new ontology. For the objective to be achieved, the following tasks must be performed: to determine the modern type of determinism, to identify the fundamental principle of neoclassical philosophy, and also to determine its main category. RESUMEN La situación en la que cae la filosofía moderna hoy es fundamentalmente diferente. Los cambios sociales y conceptuales en la ciencia filosófica moderna se refieren no solo a la revisión de la realidad, sino también a la explicación de nuevas categorías y principios. Este artículo tiene como objetivo revelar el contenido principal de los modelos reflexivos y el potencial de la filosofía neoclásica en el contexto de la formación de una nueva ontología. Para lograr el objetivo, se deben realizar las siguientes tareas: determinar el tipo moderno de determinismo e identificar el principio fundamental de la filosofía neoclásica para determinar su categoría principal.